Pengaruh Keunggulan Sumber Daya Manusia, Kualitas Pelayanan dan Keinginan Konsumen Terhadap Loyalitas Pelanggan (Studi Kasus pada Mahasiswa FEB yang Berbelanja di Indomaret) - Reza Amanullah Rusydi; Abdul Kodir Djaelani; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
AbstractThis research aims to determine the effect of Human Resource Excellence, Service Quality and Consumer Desire on Customer Loyalty in FEB Students who shop at Indomaret. This type of research uses quantitative research with data collection methods through questionnaires. The samples taken in this study were FEB Unisma students, namely 85 students. The tool used for data processing is SPSS version 26. In this research, it has been freed from the validity and reliability of the data. Tests of data analysis used for this research are normality test, classical assumption test, multiple linear regression analysis, hypothesis testing and also testing the coefficient of determination (R2). The variables used in this research are Customer Loyalty (Y), HR Excellence (X1), Service Quality (X2) and Consumer Desire (X3). The results of this study indicate that the Variables of HR Excellence, Service Quality and Consumer Desire partially and simultaneously have a positive and significant influence on Customer Loyalty at Indomaret. Keywords: Customer Loyalty, Human Resources Excellence, Service Quality